2010
DOI: 10.1002/jcu.20696
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of hepatic vein Doppler waveform and hepatic artery resistance index with the severity of nonalcoholic fatty liver disease

Abstract: As the severity of nonalcoholic fatty infiltration increases, the incidence of abnormal hepatic vein waveforms increases and hepatic artery resistance index decreases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
34
1
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(46 citation statements)
references
References 42 publications
8
34
1
2
Order By: Relevance
“…Hepatomegaly is a prevalent finding in patients with NAFLD and liver size increases as the degree of NAFLD increases [3,10,15]. In our study, similar to the medical literature, we found that liver size was increased with an increase of fatty infiltration with a statistically significant difference.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Hepatomegaly is a prevalent finding in patients with NAFLD and liver size increases as the degree of NAFLD increases [3,10,15]. In our study, similar to the medical literature, we found that liver size was increased with an increase of fatty infiltration with a statistically significant difference.…”
Section: Discussionsupporting
confidence: 88%
“…The main features of the disease, with the exception of alcohol consumption, are fatty infiltration or lipid deposition in the hepatocytes in addition to elevated liver function tests [2][3][4]. Although NAFLD is accepted as a benign disease, it can progress to non-alcholic steatohepatitis, which is the advanced state of the disease, and can be complicated with liver fibrosis, cirrhosis, and even liver failure [4][5][6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the traditional ultrasound (US) is an excellent diagnostic technique to reveal the presence of diffuse fatty liver disease, it is neither sensitive nor specific to reveal fibrosis, except in advanced stages where signs of cirrhosis are evident. Previous studies have demonstrated that hepatic artery resistive index (HARI) is significantly altered in patients with NAFLD, with significant reduction of this parameter with increasing of severity of diffuse fatty liver disease [7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, measurements are altered by disease processes that affect hepatic blood flow (right sided heart failure, vasoactive medications, post liver transplant). Diffuse fatty infiltration may also interfere with results of hepatic vein waveform and hepatic artery resistance index [14].…”
Section: Ultrasound-based Measures Of Fibrosismentioning
confidence: 99%